Critical Role of Intermediaries on Technology Transfer: Case Study of BIOTROP and Center for Mariculture Development of Lampung - Sari, Karlina; Alamsyah, Purnama; Asmara, Anugerah Yuka; Kusnandar, Kusnandar; Mulatsih, Sri (SBM ITB, 2017)
Abstract. Relationship among technology generator and technology user is one of factors determining successful technology transfer, but the existence of intermediaries is proven to enhance the absorptive capacity of technology user, especially in rural areas. Government can enact as intermediary by supporting the relationship generator-user, which is commonly found in agriculture and fishery sectors. The aim of this study is to demonstrate how government can support technology transfer from academic institution to rural industry. Using case study method, this study focused on the critical role of Center for Mariculture Development of Lampung (CMDL) which acts as an intermediary of technology transfer process from Southeast Asian Ministers of Education Organization- Southeast Asian Regional Center for Tropical Biology (SEAMEO-BIOTROP) to seaweed farmers. This study shows that intermediary agent plays an important role in articulating demand from technology user to technology generator, creating network between adopter-generator, and providing resources (fund, technician, industrial-scale laboratory) for technology commercialization. Intermediary with strong commitment to deliver technology to society is highly needed in successful technology transfer.Keywords: technology transfer, technology adoption, tissue culture, seaweed, intermediaryAbstrak. Hubungan antara penghasil dan pengguna teknologi merupakan salah satu faktor yang menentukan keberhasilan transfer teknologi, tetapi keberadaan lembaga perantara telah dibuktikan mampu meningkatkan kapasitas absorbsi pengguna teknologi, terutama di daerah pedesaan. Pemerintah dapat berperan sebagai perantara antara penghasil dan pengguna teknologi, seperti yang umum ditemukan di sektor pertanian dan perikanan. Tujuan penelitian ini adalah untuk menunjukkan bagaimana pemerintah dapat mendukung transfer teknologi dari lembaga akademis ke industri pedesaan. Menggunakan metode studi kasus, penelitian ini fokus pada peranan vital Balai Besar Pengembangan Budidaya Laut (BBPBL) Lampung sebagai perantara proses transfer teknologi dari Southeast Asian Ministers of Education Organization- Southeast Asian Regional Center for Tropical Biology (SEAMEO-BIOTROP) ke pembudidaya rumput laut. Hasil penelitian menunjukkan bahwa agen perantara memainkan peranan penting dalam menerjemahkan permintaan dari pengguna teknologi ke penghasil teknologi, membangun jaringan antara pengguna-penghasil teknologi, dan menyediakan sumberdaya (dana, teknisi, laboratorium skala industri) untuk komersialisasi teknologi. Perantara dengan komitmen kuat untuk mengantarkan teknologi ke masyarakat sangat dibutuhkan untuk keberhasilan transfer teknologi.Katakunci: transfer teknologi, adopsi teknologi, kultur jaringan, rumput laut, perantaraÂ